Giuseppe Patroni Griffi: The Beginnings of Contemporary Neapolitan Theatre - D’Amora, Mariano (Spunti e Ricerche, 2016)
Giuseppe Patroni Griffi (Naples, 27 February 1921–Rome, 15 December 2005) is an important focal point when examining twentieth-century Neapolitan playwrights and their linguistic and social ties to the city of Naples. Neapolitan theatre did not have to wait until the 1980s for a new beginning (a post Eduardo period). Patroni Griffi’s plays signalled the beginning of contemporary Neapolitan theatre. This is proved by the contents of the Neapolitan plays written by this playwright and the clear influence the themes he had introduced since 1964 (with In memoria di una signora amica) played on the works by young Neapolitan playwrights in the 1980s. The two features of Patroni Griffi’s works which I will analyse are his use of the Neapolitan language, and his relationship with Naples as a cultural centre. The factors that most mark the break from De Filippo are Patroni Griffi’s diverse relationship with Neapolitan and the type of characters he portrayed.